Corrigendum: Revealing the mechanism of Huazhi Rougan granule in the treatment of nonalcoholic fatty liver through intestinal flora based on 16S rRNA, metagenomic sequencing and network pharmacology - Yingying Liu; Yingying Tan; Jiaqi Huang; Chao Wu; Xiaotian Fan; Antony Stalin; Shan Lu; Haojia Wang; Jingyuan Zhang; Fanqin Zhang; Zhishan Wu; Bing Li; et al. (Frontiers Media S.A., 2023)
Graphical Abstract